Kajian Sex Education dalam Kitab Tarbiyah al-Aulad fi al-Islam - Nurrohmah, Widya Alfan; Suparno, Suparno (Program Studi Pendidikan Agama Islam, 2021)
Sex education still a taboo for the majority of the community, even though it is very important to making children aware of the phenomena in their bodies when they are puberty, as preventing children sexual violence which is increasingly happening. This study to provide sex education for pre-puberty children as an effort to prevent children sexual violence in Tarbiyah al-Aula>d fi> al-Islam. This study uses a literature study method using data collection techniques and documentation presented descriptively. The results showed that pre-puberty children, sexual education emphasized the ethics of asking for permission and maintaining views. Both ethics are taught using awareness, warning, and bonding to adjust the child's age in order to understand the phenomena that occur in his body when he is puberty. So in conclusion, sex education must be delivered before the child reaches puberty to know the rights and obligations as a Muslim and to prevent sexual violence.